Effect of different levels of Sage (Salvia officinalis) essential oil drenching on blood parameters, growth and reproductive performance of Saanen goat does - Zhina Abbas Mohammed (Journal of Kerbala for Agricultural Sciences, 2025)
The current investigation examined the impact of different doses of Sage extract on the complete blood count, body weight, and reproductive performance of Saanen goat does administer weekly over a 12-week period. Blood was collected third from 15 Saanen goat does and divided into three groups of five replicates. Fifteen adult Saanen goat does, aged 1 to 1.5 years and averaging 72 kg in body weight, were utilized in this investigation. T1 was administered 2 ml of distilled water per head, T2 received 40 mg/kg, and T3 received 80 mg/kg. The findings imply that after two months, Sage essential oil drenching at the tested levels did not substantially change the haematological parameters of Saanen does. Over the course of three months, Sage essential oil drenching significantly increased body weight in Saanen does, especially at the T2 level, by the end of the measurement, the effects were statistically noticeable. Although there were no notable variations in the size of the litters (T1:2.0, T2:1.6, and T3:1.5) or the rates of twinning, T2 showed the best reproductive results, with 100% conception and fertility rates (compared to 80% in T1 and T3) and 0% barrenness (compared to 20% in controls).